Pengaruh Konservatisme Akuntansi, Corporate Governance dan Financial Distress terhadap Agresivitas Pajak - Siti Masruroh; Benarda Benarda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of Accounting Conservatism, Corporate Governance, and Financial Distress on Tax Aggressiveness in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. This study uses a quantitative approach with secondary data in the form of annual financial reports of sample companies. Sampling was carried out using a purposive sampling technique, resulting in 14 companies that met the research criteria with a total of 70 observations over five years. The analysis method used is panel data regression, and testing was conducted using E-Views 12 software. The main objective of this study is to determine the extent to which conservatism practices in financial reporting, corporate governance, and the company's financial condition (in the context of financial distress) can influence the company's tendency to engage in tax aggressiveness, namely efforts to minimize the tax burden legally but aggressively. The results of the study indicate that simultaneously, the three independent variables—accounting conservatism, corporate governance, and financial distress—have a significant influence on tax aggressiveness. However, only corporate governance (as proxied by institutional ownership) and financial distress were found to have a significant influence on tax aggressiveness. In contrast, accounting conservatism and corporate governance, as proxied by managerial ownership, did not show a significant influence. These findings suggest that companies with high institutional ownership tend to be better able to control aggressive tax management practices, while financial distress encourages management to seek tax efficiency measures as a survival strategy. This research contributes to the interests of regulators and stakeholders in understanding the factors influencing tax aggressiveness in vital industrial sectors such as non-cyclical consumer goods.